Effects of process variables for NO conversion by double-layered photocatalytic mortar with TiO2 nanoparticles - Jin, Hyeon; Lee, Tae Min; Choi, Hajin; Kim, Kyo-Seon (Journal of industrial and engineering chemistry (Seoul, Korea), 2023)
[Display omitted] •A double-layered photocatalytic mortar was fabricated with TiO2 nanoparticles.•The effects of environmental variables on NO conversion were investigated.•NO conversion efficiencies were analyzed in transient environmental conditions. In this study, we prepared the double-layered photocatalytic mortar, where the top-layer has the minimum thickness of 2 mm. We investigated systematically the effects of various process variables (initial NOX concentration, TiO2 addition amount, UV-A radiation, gas flow rate and relative humidity) on photocatalytic conversion of NOX and also the transient NOX conversions for changing ambient conditions of process variables with time. The higher the nano-TiO2 concentration in the mortar or UV-A radiation intensity is, or the lower the NOX gas flow rate or relative humidity is, the higher the NOX conversion efficiency is. As the initial concentration of NOX increases, NOX conversion efficiency decreases, but the amount of NOX conversion increases. It is confirmed that the prepared photocatalytic mortar could convert NOX in the air efficiently for various conditions of process variables. NOX conversion efficiencies in transient environmental conditions were equivalent to those in fixed conditions for the same process variables. This study provides strong basic data to apply the photocatalytic mortar to convert NOX efficiently using solar energy without the use of extra energy and can be easily extended to future applications to infrastructures such as buildings, tunnels, or roads.